Intracellular Delivery of Nanoparticles and DNAs by IR9 Cell-penetrating Peptides - Liu, Betty R.; Liou, Ji-Sing; Huang, Yue-Wern; Aronstam, Robert S.; Lee, Han-Jung (PLOS ONE, 2013)
Cell-penetrating peptides (CPPs) comprised of basic amino residues are able to cross cytoplasmic membranes and are able to deliver biologically active molecules inside cells. However, CPP/cargo entrapment in endosome limits biomedical utility as cargoes are destroyed in the acidic environment. In this study, we demonstrate protein transduction of a novel CPP comprised of an INF7 fusion peptide and nona-arginine (designated IR9). IR9 noncovalently interacts with quantum dots (QDs) and DNAs to form stable IR9/QD and IR9/DNA complexes which are capable of entering human A549 cells. Zeta-potentials were a better predictor of transduction efficiency than gel shift analysis, emphasizing the importance of electrostatic interactions of CPP/cargo complexes with plasma membranes. Mechanistic studies revealed that IR9, IR9/QD and IR9/DNA complexes may enter cells by endocytosis. Further, IR9, IR9/QD and IR9/DNA complexes were not cytotoxic at concentrations below 30, 5 and 20.1 µM, respectively. Without labor intensive production of fusion proteins from prokaryotes, these results indicate that IR9 could be a safe carrier of genes and drugs in biomedical applications.